2002
DOI: 10.1037/0022-006x.70.5.1129
|View full text |Cite
|
Sign up to set email alerts
|

The use of acceptance and commitment therapy to prevent the rehospitalization of psychotic patients: A randomized controlled trial.

Abstract: Social anhedonia has been linked to the development and exacerbation of psychosis. The present study explored the hypothesis that scores in social anhedonia are related to deictic relational responding, empathic concern, and experiential avoidance, as suggested by relational frame theory and acceptance and commitment therapy. College students (N = 110) from a Spanish university completed self-report measures of social anhedonia, empathy, and experiential avoidance. Deictic relational responding was measured by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
469
2
27

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 634 publications
(512 citation statements)
references
References 69 publications
14
469
2
27
Order By: Relevance
“…The lack of any significant differences in the current study between ACT and TAU at reducing positive symptoms is consistent with previous research (Bach & Hayes, 2002;Gaudiano & Herbert, 2006). Symptom reduction per se is not a primary goal of ACT.…”
supporting
confidence: 91%
See 3 more Smart Citations
“…The lack of any significant differences in the current study between ACT and TAU at reducing positive symptoms is consistent with previous research (Bach & Hayes, 2002;Gaudiano & Herbert, 2006). Symptom reduction per se is not a primary goal of ACT.…”
supporting
confidence: 91%
“…Both were non-blind trials that focused on inpatients with psychotic disorders. Bach and Hayes (2002) found that individuals receiving ACT demonstrated significantly lower belief in positive symptoms at follow-up compared to the treatment as usual only group (TAU). The re-hospitalization rate in the ACT group was only half that of the TAU only group.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…As an applied matter, this analysis suggests practically useful forms of contextual control that can reduce the impact of negative private events without necessarily changing their form or frequency, such as acceptance and cognitive defusion. This claim has, in turn, been empirically supported by outcome studies (see Hayes, Masuda, Bissett, Luoma, & Guerrero, 2004, for a review), process analyses (e.g., Bach & Hayes, 2002;Zettle & Hayes, 1986) and component analyses (e.g., Masuda, Hayes, Sackett, & Twohig, 2004;Gutiérrez, Luciano, Rodríguez, & Fink, in press).…”
mentioning
confidence: 88%